Bandgap shifting and crystalline quality of rf-sputtered intrinsic-zno nanofilm for tfsc application - Husna J.; Menon P.S.; Chelvanathan P.; Sampe J.; Amin N.; Tripathy S.K.; Lenka T.R.; Md. Zain A.R.; Mohamed M.A. (Universiti Malaysia Perlis, 2023)
Intrinsic Zinc Oxide (i-ZnO) is a promising material and has been applied in many types of solar cell structures, and particularly in thin film solar cells (TFSC) where it is normally used as the n-type layer or as normally addressed, the buffer or window layer. In this work, ZnO nanofilm was deposited by radio frequency (RF) sputtering technique and the thickness was varied in the range of 50 to 200 nm. The overall results show that the average transmission of i-ZnO was over 70% and the band gap (Eg) obtained was in the range of 3.14 eV-3.25 eV for all nanofilms. Meanwhile, for the structural results, it was clearly shown that the crystalline size of the nanofilms have good quality, and all ZnO films exhibited a (002) diffraction peak, proving the crystallinity of the films via x-ray diffraction (XRD) data analysis. The results assume that the ZnO with various thicknesses deposited with this technique were in accordance with its expected properties and is acceptable to be utilized in TFSC application as a buffer or window layer. 2020, Universiti Malaysia Perlis. All rights reserved.